Communication Process in Implementing Qanun Number 11 of 2018 concerning Sharia Financial Institutions and Mergers of Indonesian Sharia Banks - Alief, Bisma; Luqman, Yanuar (Kanal: Jurnal Ilmu Komunikasi, 2024)
In implementing Sharia banking in Indonesia, especially in Aceh, several obstacles have emerged, such as the low level of public financial literacy, the conventional bank conversion process, supervision and regulation, changes in corporate culture, and uniformity and harmonization of Sharia banking regulations. This research aims to examine and understand the communication process in the implementation of Qanun No. 11 of 2018 concerning Sharia Financial Institutions and the merger of Bank Syariah Indonesia. This research uses a descriptive qualitative method with a case study approach. Data collection was carried out in-depth and involved various sources of information, including observations, interviews, audiovisual materials, and related documents and reports. The research results highlight the importance of effective communication in dealing with change within an organization or company. Converting a conventional bank to a Sharia bank in Aceh requires a persuasive approach and efforts to create a conducive internal climate, while the Bank Syariah Indonesia merger process shows the importance of thorough communication preparation and an effective branding strategy. Establishing a new organizational structure requires the use of methods such as chair-sharing meetings and performance-based assessments. Adopting a new corporate culture, "BSI One Culture," shows how important continuous efforts are in facilitating employee adaptation and minimizing obstacles that arise. By focusing on open, strategic, and persuasive communication, Bank Syariah Indonesia successfully completed the conversion and merger process, creating operational continuity and a new corporate culture in Aceh.